(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Head, neck and face swellings constitute a major proportion of palpable swellings. It occurs in individuals of all ages and includes various types of inflammatory, developmental, and neoplastic pathological lesions. Fine needle aspiration cytology (FNAC) is safe, reliable and has easy pre-operative access to these swellings and is utilized as an effective tool beforehand in surgical cases. The purpose of this study is to correlate FNAC diagnosis of head neck and face swellings with the histopathological examination (HPE) which is considered a gold standard. Material and methods: A prospective study is carried out in the cytology section of the pathology department of tertiary care hospital. A total of 1020 FNAC are performed, out of which 224 cases of Head neck and face swellings were included in the study. Cases with inadequate FNAC cellularity were excluded from the study. After assessing clinical and cytomorphological details, a diagnosis was made. Their correlation with the histopathological examination was done wherever possible. Results: Out of 224 FNAC lesions, the lymph node (50%) was the commonest site of aspiration followed by the thyroid (37%), salivary glands (7%) and others/miscellaneous sites (6%). 39 cases were neoplastic and 185 were non-neoplastic. Histopathological correlation was made in 93 (41.51%) cases. The diagnostic accuracy was 97.85%, sensitivity was 98.68%, specificity was 94.12%, positive predictive value was 98.68% and negative predictive value was 94.12%. Conclusion: Fine needle aspiration cytology provides minimally invasive, out-patient, and rapid cytological diagnosis in head neck and face swellings. It is time proven technique. It is extensively reliable for making a definitive diagnosis, with limitations. FNAC is clearly not substituted for histopathology but can be utilized as an adjunct.